Topology optimization for disc structures with buckling and displacement constraints. Issue 1 (2nd January 2023) - Wang, Weiwei; Ye, Hongling; Li, Zonghan; Sui, Yunkang
Abstract : This article presents a novel topology optimization framework, which takes the key nodal displacements and the critical buckling load factor as constraints to guarantee that the designs of torsional disc structures not only satisfy the resistant capability of in-plane deformation but also do not cause out-of-plane buckling failure. The composite exponential filter functions and Taylor expansion are applied to obtain the approximate explicit functions between structural performance and topological design variables based on the results of static and buckling analyses. The dual-sequence quadratic programming algorithm is applied to solve the explicit topology optimization model. In addition, an adaptive image filter technology is developed to overcome the numerical instability problem that occurs in the finite element model of discs with significant changes in mesh size. Finally, some designs of torsional disc structures are presented to illustrate the effectiveness and feasibility of this method.